1974
DOI: 10.1182/blood.v43.4.591.591
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Megakaryocytes From Mouse Bone Marrow by Velocity Sedimentation

Abstract: A technique for separating mouse bone marrow megakaryocytes by unit gravity velocity sedimentation is described using a modified sedimentation chamber. The velocity sedimentation profile for megakaryocytes comprises three peaks corresponding to sedimentation velocities of 30, 60, and 100 mm/hr. Morphologic examination of megakaryocytes in the 30 mm/hr peak reveals them to be primarily immature with the latter two peaks corresponding to larger, more mature megakaryocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

1976
1976
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 7 publications
0
29
0
1
Order By: Relevance
“…Platelets are formed from the cytoplasm of megakaryocytes (MKs), their precursor cells, which reside in the bone marrow (Pease, 1956). MKs are the largest (50–100 µm) and also one of the rarest cells in the bone marrow; MKs account for ∼0.01% of nucleated bone marrow cells (Nakeff and Maat, 1974). To assemble and release platelets, MKs become polyploid by endomitosis (DNA replication without cell division) and then undergo a maturation process in which the bulk of their cytoplasm is packaged into multiple long processes called proplatelets, and the nucleus is extruded.…”
Section: Introductionmentioning
confidence: 99%
“…Platelets are formed from the cytoplasm of megakaryocytes (MKs), their precursor cells, which reside in the bone marrow (Pease, 1956). MKs are the largest (50–100 µm) and also one of the rarest cells in the bone marrow; MKs account for ∼0.01% of nucleated bone marrow cells (Nakeff and Maat, 1974). To assemble and release platelets, MKs become polyploid by endomitosis (DNA replication without cell division) and then undergo a maturation process in which the bulk of their cytoplasm is packaged into multiple long processes called proplatelets, and the nucleus is extruded.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to compare our work to others whose methods are different and whose experimental conditions and/or quantitative apprecipation of cell recovery are not very precise (Haskill et a1 1972, Nakeff & Maat 1974, Zeiller et a1 1976, Sulc et a1 1977, Wells et a1 1977a/b, Burghouts et a1 1977, 1978.…”
Section: Discussionmentioning
confidence: 95%
“…Several methods have been reported to be useful in the separation and enrichment of megakaryocytes and their precursors. Velocity sedimentation and centrifugal elutriation have been particularly useful for the enrichment of mature megakaryocytes because of their large size (Nakeff and Maat, 1974;Pretlow and Stinson, 1976;Worthington and Nakeff, 1981). A combination of density centrifugation in gradients of bovine serum albumin (BSA) and velocity sedimentation has made it possible to enrich for the small AchE positive cell, the earliest histochemically identifiable cell in the megakaryocytic lineage (Long et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…AchE is an enzyme which has been shown to be relatively specific for the megakaryocytic lineage in rodents, and can be identified in small cells which are unrecognizable as megakaryocytes by standard morphologic features (Jackson, 1973;Long and Henry, 1979;Long and Williams, 1981). Techniques for the separation and partial isolation of these classes of megakaryocytes have been described (Nakeff and Maat, 1974;Leif et al, 1975; 0 1985 ALAN R. LISS, INC Levine and Fedorko, 1976;Nakeff and Floeh, 1976;Pretlow and Stinson, 1976;Nachman et al, 1977;Sitar et al, 1977;Rabellino et al, 1979;Levine, 1980;Worthington and Nakeff, 1981;Williams et al, 1981;Long et al, 1982;Sitar, 1984). Rabellino et al (1979) found that mature human megakaryocytes are found at the top of discontinuous Percoll gradients at low density (less than 1.050 g/cm3).…”
mentioning
confidence: 99%